Annual Report on Exchange Arrangements and Exchange Restrictions 2018. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
The Annual Report on Exchange Arrangements and Exchange Restrictions has been published by the IMF since 1950. It draws on information available to the IMF from a number of sources, including that provided in the course of official staff visits to member countries, and has been prepared in close consultation with national authorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Investment Decisions; Monetary Policy; Portfolio Choice